Promoting Malaysia medical tourism through MyCREST oriented retrofitted hospitals - Ohueri, Chukwuka Christian; Nwobodo, Stanley; Enegbuma, Wallace Imoudu; Habil, Hadina (Penerbit Universiti Kebangsaan Malaysia, 2019)
Globally, Malaysia is recognized among the best destinations for medical tourism. According to Malaysia Healthcare Travel Council (MHTC), about 1,050,000 medical tourists across the globe visited Malaysia in 2017, generating over RM1 billion revenue for Malaysia. Nevertheless, previous studies have affirmed that majority of the existing hospitals used for medical tourism in Malaysia have not been evaluated with Green Building Assessment Tools (GBATs) such as the Malaysian Carbon Reduction and Environmental Sustainability Tool (MyCREST). This places uncertainty in the long term effect on sustainable ecosystems and eventual improvement in the medical tourist experience. Therefore, the aim of this conceptual paper is to develop MyCREST Oriented Retrofitting Framework (MORF), to reduce the environmental impact of existing hospitals, enhance the comfort, productivity, and health of the medical tourists in Malaysia. To achieve the aim, this research conducted a Systematic Literature Review (SLR) of about 100 articles published in reputable journal within the last 3 decades (1987 – 20018). Also, the overarching MyCREST Reference Guide was evaluated via document analysis. This enabled the critical reflection and holistic understanding of the nexus between MyCREST embedded retrofitted hospitals and Malaysia medical tourism. As a result, a five-phase MORF: Hospital Project Set up and Pre-Retrofit Survey, Carbon Foot Print Auditing, MyCREST Oriented Retrofit, Implementation and Commissioning, and Validation and Verification was developed. The findings of this research will enhance the sustainable performance of existing hospitals, and enlighten the MHTC, construction experts, and other stakeholders on the importance of sustainable hospitals towards attracting more medical tourists to Malaysia.